Pengaruh Perkembangan Ekspor, Impor dan Jumlah Umkm Terhadap Pertumbuhan Ekonomi Di Provinsi Jawa Timur Tahun 2013-2023 - Irmajaya, Elistrida; Maulana, Alfin; Nanda, Aditya Surya; ., Fitryani; Bayu Murti, Agung; Edi, Agus Sarwo (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This research aims to analyze the impact of exports, imports, and the number of SMEs on economic growth in East Java during the period 2013–2023. The importance of providing solutions to the issues of exports, imports, and the number of SMEs related to economic growth in East Java. Using a quantitative approach with panel data regression analysis method using Fixed Effect Model (FEM) on data from 38 districts/cities in East Java. The results show that the export variable has a significant negative impact on economic growth, indicating that the increase in exports has not been able to drive the regional economic growth because the exported products are raw materials. The import variable has a significant positive impact on economic growth, due to imported products being capital goods and raw materials that support increased economic productivity. The number of SMEs has a significant negative impact on economic growth, reflecting the still low contribution of micro and informal enterprises due to their quality and production capacity. The East Java government is expected to improve the export of finished goods and provide training and support to SMEs so that the produced products have added value and competitiveness. This finding highlights the importance of enhancing export quality and strengthening SME capacity to drive more sustainable regional economic growth.